2017
DOI: 10.3390/su9060893
|View full text |Cite
|
Sign up to set email alerts
|

An Agent-Based Model to Project China’s Energy Consumption and Carbon Emission Peaks at Multiple Levels

Abstract: Abstract:To assess whether China's emissions will peak around 2030, we forecast energy consumption and carbon emissions in China. We use an agent-based model driven by enterprises' innovation. Results show some differences in both energy consumption peaks and carbon emission peaks when we compare trends at different levels. We find that carbon emissions and energy consumption will peak in 2027 and 2028, respectively. However, the primary, secondary, and tertiary industries will reach energy consumption in diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Assume thatα,β,γ are the parametric estimated values of Equation (14), replacing t e (t + 1) =αt (1) e (t) +βt +γ, to minimise the simulation error, the following condition needs to be satisfied:…”
Section: Homologous Grey Energy Prediction Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Assume thatα,β,γ are the parametric estimated values of Equation (14), replacing t e (t + 1) =αt (1) e (t) +βt +γ, to minimise the simulation error, the following condition needs to be satisfied:…”
Section: Homologous Grey Energy Prediction Modelmentioning
confidence: 99%
“…In Section 2, we build a new grey prediction model, HGEM (1,1). In Section 3, we study the error-checking method for the HGEM(1,1) model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How to realize this promise without compromising the socio-economic development has become an important issue that needs to be solved urgently. Therefore, empirical analysis and projection on carbon emissions are useful for the government to provide a theoretical and scientific basis for the sustainable development of low-carbon economy [4].At present, the research on energy-related carbon emissions are mainly classified as the calculation of carbon emissions [7-9], analysis of decomposition methods and influencing factors [5,10,11], scenarios analysis and prediction of carbon emissions [12][13][14][15], the application of technology and policy simulation to reduce carbon emissions [16][17][18]. Moreover, the studies on influencing factors is a critical field to make projection and reduction policies for carbon emissions [5].…”
mentioning
confidence: 99%
“…It has advantages of comprehensive analysis and is considered as an established carbon emissions model which has been used widely [5,19,28,29].Under the background of carbon emissions peak, several scholars focused on the STIRPAT model to analyze and project carbon emissions, thus assisting Chinese policymakers to formulate reasonable sustainable approach of socio-economic development. These studies suggested that Chinese carbon emissions will peak between 2020 and 2030 [4,14,15,34]. However, the national carbon emissions peak would not mean that provincial emissions status at the regional-level [5].…”
mentioning
confidence: 99%